Changes in Content of Polyphenols and Ascorbic Acid in Leaves of White Cabbage after Pest Infestation - Zuzana Kovalikova; Jan Kubes; Milan Skalicky; Nikola Kuchtickova; Lucie Maskova; Jiri Tuma; Pavla Vachova; Vaclav Hejnak (Molecules, 2019)
Crops, such as white cabbage (Brassica oleracea L. var. capitata (L.) f. alba), are often infested by herbivorous insects that consume the leaves directly or lay eggs with subsequent injury by caterpillars. The plants can produce various defensive metabolites or free radicals that repel the insects to avert further damage. To study the production and effects of these compounds, large white cabbage butterflies, Pieris brassicae and flea beetles, Phyllotreta nemorum, were captured in a cabbage field and applied to plants cultivated in the lab. After insect infestation, leaves were collected and UV/Vis spectrophotometry and HPLC used to determine the content of stress molecules (superoxide), primary metabolites (amino acids), and secondary metabolites (phenolic acids and flavonoids). The highest level of superoxide was measured in plants exposed to fifty flea beetles. These plants also manifested a higher content of phenylalanine, a substrate for the synthesis of phenolic compounds, and in activation of total phenolics and flavonoid production. The levels of specific phenolic acids and flavonoids had higher variability when the dominant increase was in the flavonoid, quercetin. The leaves after flea beetle attack also showed an increase in ascorbic acid which is an important nutrient of cabbage.